The Selfie Paradox: Nobody Seems to Like Them Yet Everyone Has Reasons to Take Them. An Exploration of Psychological Functions of Selfies in Self-Presentation - Diefenbach, Sarah; Christoforakos, Lara (Frontiers in Psychology, 2017)
Selfies appear as a double-edged phenomenon. Taking, posting, and viewing selfies has become a daily habit for many. At the same time, research revealed that selfies often evoke criticism and disrespect, and are associated with non-authenticity and narcissism. The present study (N = 238) sheds further light on the somewhat contradictory phenomenon of selfies and their psychological value. In addition to previous studies on selfies and personality traits, the present research explores relations to popular, habitual self-presentation strategies, self-reflections on own and others’ selfie-taking behavior, selfie-related affect, and perceived consequences of selfies, by applying a combination of self-constructed and existing scales [e.g., habitual self-presentation scales (Merzbacher, 2007), Positive and Negative Affect Schedule (Watson et al., 1988)]. Our findings confirmed habitual self-presentation strategies as a relevant factor for understanding selfies: Participants scoring high on self-promotion (promoting one’s strength and abilities) and self-disclosure (revealing one’s feelings for earning sympathy) felt especially positive while takings selfies, whereas understatement was correlated with negative feelings. Nevertheless, self-presentational motives were rather attributed to others’ selfies than to own selfies. Moreover, others were assumed to have more fun and positive feelings while taking selfies whereas own selfies were judged as more authentic and self-ironic. Altogether, participants expressed a distanced attitude toward selfies, with stronger agreement for potential negative consequences (threats to self-esteem, illusionary world) than for positive consequences (e.g., relatedness, independence), and a clear preference (82%) for viewing more usual pictures instead of selfies in social media. The revealed selfie-bias, i.e., the systematic discrepancy between judgments on own versus others’ selfies, and the reported critical attitude toward selfies allows multiple interpretations. Taking peoples’ statements literally, selfies should have never become as popular as they actually are. On the other hand, the selfie bias may fulfill a psychological function. Perceiving one’s own selfie behavior as self-ironic and only half-committed, allows to fulfill self-presentational needs without feeling narcissistic. In conclusion, we suggest that the playful and somewhat ambiguous support of self-presentation may be a key factor for the success of selfies. Relations to biases and mechanisms from social psychology, limitations of the present study and implications for future research are discussed.